Professionals in food chains EurSafe 2018, Vienna, Austria, 13-16 June 2018 - Springer, Svenja; Grimm, Herwig 1978- (Wageningen Academic Publishers, 2018)
Within the public debate surrounding food, people often contend that the key to meeting current challenges is changing consumer behaviour. Professionals and practitioners such as farmers, retailers, veterinarians, or researchers only occupy the limelight during media coverage of so-called 'food scandals'. If we are to better understand and negotiate current and future problems in the food supply chain, it will be essential to pay more attention to the role and position of professionals involved. 'Professionals in food chains' addresses questions as: What are the main ethical challenges for professionals in the food supply chain? Who within this complex field holds responsibility for what? What does it mean for the food-related professions to operate in an atmosphere of immense social tension and high expectations? Which virtues are required to do a 'good' job? In brief: What can be said about the roles, responsibilities, and ethics of professionals across this dynamic field? This book brings together work by scholars from a wide range of disciplines, addressing a broad spectrum of topics pertaining to professionals in the food supply chain. Topics covered include general issues on professional roles and responsibility, sustainable food supply chains, novel approaches in food production systems, current food politics, the ethics of consumption, veterinary ethics, pedagogical/educational and research ethics, as well as aquacultural, agricultural, animal, and food ethics.